Monitoring Chinese table tennis players physical function preparing for the Swedish World Table Tennis Championships - Liu, W.; Xu, X. (Exercise Biochemistry Review, 2018)
Objective In this paper, five people of the national table tennis men's team are selected as the research objects, and the blood biochemical index of the athletes are measured and analyzed. To understand and master the current physical fatigue and physical function recovery of key athletes based on the test results, and provide reasonable training program and sports nutrition supplements advice for key athletes, so that athletes can achieve the best physical condition, improve training effect and performance.